Waterloo. L'Eglise - The church, GP076273 - Auteur inconnu (Wikimedia Commons, 1922)
Carte postale ancienne issue de Wikimedia Commons. Titre: Waterloo. L'Eglise - The church, GP076273. Title Waterloo. L'Eglise - The church Date ca. 1922 Publisher Bruxelles: Thill Uniform title Waterloo. Gebouwen. Kerken en kapellen Series Belgique. Province du Brabant wallon. Cartes postales Belgium. Province of Walloon Brabant. Postcards België. Provincie Waals Brabant. Prentkaarten Genre Post cards Extent 1 kaart / postcard Graphic Black-and-white Language French Additional info General note: Titelgegevens ontleend aan prentkaart General note: Met extra tekstinformatie op de kaart Source Library Catalog Source ID lbsn9992774666301471
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église